Identification of novel inhibitors against hantaviruses through 2D fingerprinting and molecular modeling approaches - Alshammari, Abdulrahman (Frontiers in Immunology, 2023)
With the immense growing outbreaks of Hanta virus with still no effective treatment available. There is an urgent need of exploring new computational approaches which will target potential virulent proteins that will eventually reduce its growth. Here, in this study an envelope glycoproteins Gn was targeted. The glycoproteins, which are the sole targets of neutralizing antibodies, drive virus entry via receptor-mediated endocytosis and endosomal membrane fusion. Here in this study inhibitors are proposed to negate its action mechanism. Favipiravir an already used FDA compound against Hantavirus, on the basis of its scaffolds a library was designed using a 2D fingerprinting approach. Upon molecular docking analysis top-4 docked compounds (i) (Favipiravir (-4.5 kcal/mol) (ii) N-hydroxy-3-oxo-3, 4-dihydropyrazine-2-carboxamide (-4.7 kcal/mol) (iii) N, 5, 6-trimethyl-2-oxo-1H-pyrazine-3-carboxamide (-4.5 kcal/mol) (iv) 3-propyl-1H-pyrazin-2-one (-3.8) were prioritized on the base of lowest binding energies score. Through molecular docking, the best-categorized compound was subjected to molecular dynamics simulation for a 100 ns time span. Molecular dynamics sheds light on each ligand behavior within the active site. Among four complexes only Favipiravir and 6320122 compound found to be stable inside the pocket. This is due to the presence of common rings pyrazine and carboxamide ring which make signigicant interaction with active key resdidues Furthermore, the MMPB/ GBSA binding free energies analysis calculated for all complexes which supported the dynamics results by calculating the most stable values for Favipiravir complex ( -9.9933 and -8.6951 kcal/mol) and for 6320122 compound complex (-13.8675 and -9.3439 kcal/mol) which demonstrated that the selected compounds have a proper binding affinity with targeted proteins. Similarly hydrogen bond analysis reveals strong bondng interaction. Results yielded strong interaction between the enzyme and the inhibitor throughout the simulation thus the inhibitor has the potential to become a lead compound and could be subjected to experimental evaluation to unveil their blockage ability.